Challenges to diabetes self-management for adults with type 2 diabetes in low-resource settings in Mexico City: a qualitative descriptive study - Robin Whittemore; Mireya Vilar-Compte; Selene De La Cerda; Denise Marron; Rosabelle Conover; Roberta Delvy; Annel Lozano-Marrufo; Rafael Pérez-Escamilla (BMC, 2019)
Abstract Background The prevalence of type 2 diabetes (T2D) in Mexico is one of the highest in the world, with high morbidity and mortality, and difficulty meeting glycemic targets. The purpose of this study was to identify the challenges for T2D self-management as perceived by both adults with T2D and health care providers in primary health clinics from Seguro Popular in Mexico City. Methods This was a qualitative descriptive study conducted in three Seguro Popular primary care clinics in Mexico City using convenience sampling. Semi-structured interviews were conducted with participants and data were analyzed using a content analysis approach. Results The sample included 20 adults with T2D [52.5 years old (SD = 9.9), diagnosed with T2D for 12.3 years (SD = 6.3), mean A1C of 9.8% (SD = 2.4), 80% female, 90% with financial insecurity] and 19 providers [primarily female (78.9%), mean age of 41.6 years old (SD = 11.4), 12.3 mean years in practice (SD = 8.50)]. Personal challenges included cultural beliefs, lack of resources, challenges to lifestyle modification, lack of family support/competing demands, and mental health issues. System level challenges included lack of resources, perceived quality of care, and patient engagement barriers. Conclusions Evidence-based diabetes self-management programs need to become more accessible, taking into consideration the social determinants of health and building upon current initiatives to improve early diagnosis and treatment of T2D. Cultural beliefs, personal control, and low health literacy influence diabetes self-management in adults with T2D with limited resources. Mental health and financial challenges of adults with T2D will require multidisciplinary team-based care. Future research on best practices to implement and scale-up evidence-based patient-centered T2D prevention and DSME programs for the poor and underserved is warranted in Mexico and world-wide.